Aldo van Eyck and Louis I. Kahn: Parallels in the Other Tradition of Modern Architecture - McCarter, Robert (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
In September 1959, at the invitation of Alison and Peter Smithson, the American architect Louis I. Kahn (1901-1974) attended the 11th and last Congrés Internationaux d’Architecture Moderne (CIAM) conference held at Henry van de Velde’s Kroller-Muller Museum in Otterlo, the Netherlands. There he met the Dutch architect Aldo van Eyck (1918-1999), founding member of Team 10, the successor of CIAM that emerged at the end of this conference. The paths of these two architects – the Second-Generation modernist Kahn, then 58 years old, and the Third-Generation modernist Van Eyck, then 40 years old – parallel in so astonishingly many ways, crossed here for the first time, deeply affecting them both at a time of critical transition in their respective practices and thought.
Keywords: Aldo van Eyck; Louis I. Kahn; Modern Architecture